Effects of Corruption, Government Effectiveness and Political stability on Economic Growth: Evidence from Morocco - Ritahi, Oussama; Echaoui, Abdellah (International Journal of Economics and Financial Issues, 2024)
This study examines the impact of Corruption, government effectiveness and political stability on economic growth in Morocco. We conduct an empirical analysis to quantify the impact of institutional quality on economic growth over the period 1996 – 2021 by employing Two Stage Least Squares (2SLS). The findings reveal that corruption has a significant negative influence on economic growth, highlighting the importance of anti-corruption measures. On the other hand, political stability emerges as a key driver of economic growth, emphasizing the need for stable political environments to attract investments and foster entrepreneurship. Additionally, the growth of the public spending negatively affects GDP per capita, stressing the significance of prudent fiscal policies and effective public sector management. This research emphasizes the critical role of institutions, political stability, and efficient governance in driving economic growth. Policymakers can leverage these insights to enhance these institutional quality indicators and foster sustainable and inclusive economic development.